Faktor yang Mempengaruhi Kepatuhan Bidan Desa Melaksanakan Rujukan Kehamilan Risiko Tinggi (Studi Kasus di Kabupaten Kudus) - Stanislaus Kristiyanto; Henry Setyawan; Ariawan Soejoenoes; Suharyo Hadisaputro; Budi Palarto (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background: Pregnancy is a high risk of having a high probability of experiencing maternal mortality events. In the procedure management of high risk pregnant women, midwives are required to perform high-risk pregnant women referral to higher care unit. The purpose of this study was to determine some of the factors that affect adherence midwives in performing high-risk pregnancy referrals.Methods: The study was observational analytic cross-sectional design. Sampling proportionate stratified random sampling. Total sample is 60 midwives. The research instrument was a questionnaire. Data analysis using univariate, bivariate (chi-square) and multivariate (logistic regression).Results: The variables that proved influential is the detection of high-risk pregnancy competence good (PR = 0.2; p = 0.023) and age midwife more than 28 years (PR = 0.2; p =0.024). Variables that are not proven effect is the level of education, years of service, supervision supervisor, employment status, work motivation, perceptions of workload, perceived benefits, leadership perceptions and perceptions of the profession midwife.Conclusion: Factors that influence the adherence proved midwives carry out the referral of high-risk pregnancy is high risk pregnancy detection competence good and village midwives age more than 28 years with a probability of 66.0% to obey.